EFFECTS OF DEFAUNATION AND METHIONINE IN THE PRESENCE OF PROTOZOA ON THE FLOW OF MICROBIAL LONG CHAIN FATTY ACIDS FROM THE RUMEN OF SHEEP - Damry Damry (Universitas Tadulako, 2009)
This study was designed to investigate the effects of the presence or absence of protozoa in the rumen, and of methionine supplement when protozoa are present in the rumen, on microbial production of LCFA. The study used 12 first-cross Merino x Border Leicester wethers (2 years old) with body weights of between 35 and 44 kg, each was equipped with both rumen and abomasum cannulas. All sheep were offered a mix of 400 g of oaten chaff + 400 g of lucerne chaff per day which was delivered in 24 equal portions at hourly intervals via an overhead automatic-feeding machine. Digesta flow was measured using chromium ethylenediamine tetra-acetic acid (CrEDTA) complex and dietary acid-insoluble ash (AIA) as the liquid- and particle-digesta marker, respectively. All sheep were firstly defaunation using detergent alkanate 3SL3, and 8 of them were refaunated with a fresh rumen liquid obtained from a normal donor animal. Thus, there were 8 animals in the refaunated group at the commencement of study, 4 of which were intended to receive methionine supplement. However, comparison of refaunated sheep with or without methionine supplement is based on only 3 sheep per cell; 2 animals (1 of the methionine-supplemented and 1 of the methionine-unsupplemented group) were suitable to be included in the analysis. Comparison of defaunated and refaunated sheep was based on 4 sheep per cell. The study showed that the daily flow of dry matter through the abomasum was higher (P<0.05) in refaunated animals, despite the lower liquid outflow rate in these sheep. The concentration of LCFA in total digesta dry matter was not affected (P>0.05) by the presence or absence of protozoa in the rumen. However, the presence of protozoa increased concentration of LCFA in particle-digesta dry matter (P=0.081), the ruminal production (P<0.05) and daily flow of LCFA (0.01). Methionine supplementation did not alter (P 0.05) the concentration of LCFA in digesta, but significantly reduced (P<0.05) the flow of LCFA to abomasum.